Incorporation of large-scale pumped storage hydro with renewable energy sources - Gu, Nan. (2011)
This report presents the research results obtained by the author in his Final Year Project No. W1148-102: Incorporation of large-scale pumped storage hydro with renewable energy sources. It is well-known that large-scale pumped storage hydro can store surplus electrical power and release the stored energy when necessary through salient-pole synchronous generator. The working condition of the pumped storage hydro is based on the system requirements.